Telomere Length Is Associated With Adverse Atrial Remodeling in Patients With Atrial Fibrillation - Kabita Pradhan; Balram Neupane; Paul Niehues; Martin Kirschner; Fabian Beier; Chao‐Chung Kuo; Erika Anneliese Hilbold; Christian Bär; Oana‐Maria Thoma; Maximilian Waldner; Margherita Vieri; Tim H. Brümmendorf; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Atrial fibrillation (AF) is the most common cardiac arrhythmia with a massive burden on global health. The prevalence of AF increases dramatically with age and can be up to 18% in patients older than 80 years. Telomeres, which are short, repeated DNA sequences at the end of chromosomes, are known to act as a biological aging marker. In this study, we investigated the relation of telomere shortening and AF in the context of atrial remodeling. Furthermore, we assessed changes in the gene expression profiles of patients with AF according to telomere length (TL) and left atrial fibrosis. Methods We included 72 patients undergoing catheter ablation for AF. Bipolar voltage maps were obtained to determine left atrial low voltage areas as a surrogate for atrial fibrosis. TL was quantified and correlated to low voltage areas. 3′ mRNA sequencing was performed for gene expression profiling. Clonal hematopoiesis of indeterminate potential was assessed by next generation sequencing. Telomerase reverse transcriptase knockout (Tert−/−) and telomerase RNA component knockout (Terc−/−) mice were used to investigate the mechanistic impact of telomere shortening on atrial remodeling. Results Patients with advanced left atrial fibrosis had shorter telomeres compared with patients with healthy left atria. Furthermore, there was a strong correlation between the extent of left atrial low voltage areas, TL, and outcome after catheter ablation of AF. 24 months after ablation, only 26.5% of patients with advanced fibrosis and short TL were in sinus rhythm compared with 62.5% of patients with no/low fibrosis and long TL. Gene expression profiles and clonal hematopoiesis of indeterminate potential frequency differed in patients with AF with short and long telomeres. Finally, atrial tissue of mouse models with shortened telomeres showed marked left atrial fibrosis and over‐expression of fibrosis‐related genes. Conclusions Telomere shortening is correlated with left atrial remodeling. Shorter telomeres are associated with a series of molecular events which could eventually lead to cardiac fibrosis and perpetuate AF.